Evolusi Kerajaan Safawi di Persia dan Para Tokoh di Baliknya - Apip, M.; Jezy, Ahmad; Roza, Ellya (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to analyze the history of the establishment of the Safawi Kingdom and then also analyze the evolution of the Safawi Kingdom and the Islamic civilization in Persia that has been built during the Safavid Kingdom's reign. The method used is by discussing library research, which is collecting relevant data with a focus on discussion based on the literature that is the source of the data. Then it is analyzed by means of content analysis. The results found show that the efforts that have been made by the Shafawi Kingdom in building Islamic civilization in Persia can be seen from various aspects, such as politics, art, economics and science. At the beginning of its establishment, Safawi was a religious order movement that aimed to combat disbelievers and heretics. Gradually the Safavid order began to enter political movements, finally in 1501 AD succeeded in establishing a kingdom. Persian relations with Arabs in the past, have created a new element in Islamic civilization in Persia. During the Arab conquest of Persia. There was an alculturation between Arab elements and Persian elements. This alculturation can be seen from the various forms of civilization that have been formed. Although the civilization was destroyed by the Mongol attack, thanks to the emergence of the Safavid Kingdom, Islamic civilization in Persia was successfully rebuilt.